Mongol Ulsyn šinzhlėh uhaany bajguullagyn tüüh (1921-1940) - Batdorž, Čagdarsümbėrėlijn (Čingis Haan Ündėsnij Muzej, 2023)
History of Mongolian scientific organizations covering the period between 1921 and 1940